BUILDING A “SOVEREIGN INTERNET”: RUSSIA’S DIGITAL POLICIES AS A TOOL OF CENSORSHIP AND SOCIAL CONTROL - Güvenç, Sude (Public Management and Policy, 2025)
Russia has increasingly focused on developing comprehensive digital policies aimed at establishing “digital sovereignty” which seeks to reduce dependence on foreign technologies, internet infrastructure, and multinational platforms. These policies integrate internet governance, media regulation, cybersecurity, and content monitoring under the overarching concept of “information security”. The state’s digital strategy is historically rooted in Cold War-era concerns, including military-industrial competition, national identity preservation, and control over information flows. In recent years, Russia’s digital policies have intensified in response to domestic economic stagnation, political crises, and social movements that challenge the legitimacy of the regime. This study employs a mixed-methods approach combining the analysis of legal documents, policy papers, official statements, international indices, and datasets on internet censorship, online prosecutions, and digital surveillance. It examines how Russia’s digital sovereignty policies – including the Sovereign Internet Law, Yarovaya amendments, VPN restrictions, and mandatory data localization – impact freedom of speech, privacy, and access to information. The research demonstrates that while these measures are framed as necessary for national security, they enable broad censorship, state surveillance, and the suppression of civil liberties. Furthermore, Russia’s model reflects a form of “digital authoritarianism” which relies on both legal frameworks and technical measures to control the internet, regulate content, and influence public opinion. The findings underscore that Russia’s prioritization of regime stability over citizens’ rights has significant implications for freedom of expression, human rights, and global internet governance, highlighting a growing tension between national security imperatives and digital freedoms.